2021
DOI: 10.1183/13993003.01209-2021
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and COVID-19 risk: a systematic review and meta-analysis

Abstract: BackgroundIndividual case series and cohort studies have reported conflicting results on the vulnerability to and risk of mortality of people with asthma from COVID-19.Research QuestionAre people with asthma at a higher risk of being infected, hospitalised or of poorer clinical outcomes from COVID-19?MethodsA systematic review and meta-analysis based on five main databases including the WHO COVID-19 database between December 1, 2019 to July 11, 2021 on studies with a control (non-asthma) group was conducted. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
2
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 77 publications
(31 reference statements)
6
51
2
8
Order By: Relevance
“…This suggests that prompt diagnosis and effective preparation for oxygen demand may affect patient mortality when treating patients with COVID-19 and chronic obstructive airway diseases. Several studies have shown that asthma has no effect on the severity of COVID-19, and that ACO and COPD seem to be increased the mortality and morbidity of COVID-19 [ 21 22 23 ]. Nonetheless, the CDC still reports that “severe asthma” is associated with the severity of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that prompt diagnosis and effective preparation for oxygen demand may affect patient mortality when treating patients with COVID-19 and chronic obstructive airway diseases. Several studies have shown that asthma has no effect on the severity of COVID-19, and that ACO and COPD seem to be increased the mortality and morbidity of COVID-19 [ 21 22 23 ]. Nonetheless, the CDC still reports that “severe asthma” is associated with the severity of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analyses have investigated the association between asthma and COVID-19 mortality in the whole regions [1] , [2] , [3] , but the conclusions were inconsistent, which might suffer limitations from substantial variation of asthma prevalence among different countries. Moreover, a previous meta-analysis by Sunjaya et al reported that COVID-19 patients with asthma had a significantly increased risk for mortality in Asia, but not in Europe, North America and South America [4] . Taken together, those urged us to investigate the association between asthma and COVID-19 mortality in a specific country or region.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, the restrictions imposed by COVID‐19 pandemic have severely affected the management of asthma. According to the results of the two systematic reviews, the risk of SARS-CoV-2 infection and mortality after infection for asthma sufferers are reduced compared with non-asthma patients [ 33 , 34 ]. However, a Korean cohort study shows that the incidence of asthma is related to the severity and mortality of COVID-19 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%